Prescription of Kampo Formulations for Pre-natal and Post-partum Women in Japan: Data From an Administrative Health Database - Suzuki, Satoko; Obara, Taku; Ishikawa, Tomofumi; Noda, Aoi; Matsuzaki, Fumiko; Arita, Ryutaro; Ohsawa, Minoru; Mano, Nariyasu; Kikuchi, Akiko; Takayama, Shin; Ishii, Tadashi (Frontiers in Nutrition, 2021)
Introduction: Traditional Japanese (Kampo) medicines are often prescribed for women in Japan before, during, and after pregnancy. However, detailed information on the actual frequency of use and safety of Kampo preparations during pregnancy is lacking. Aim: To investigate the frequency of prescription of Kampo medicines for pregnant women in Japan. Methods: Information on Kampo medicines prescribed during outpatient care and hospitalization of selected mothers from January 2005 to August 2016 were extracted from the Japan Medical Data Center (Tokyo, Japan), which is a large claims database. Results: Of the 33,941 subscribers identified from the database, 16,294 (48%) received at least one prescription of a Kampo medicine. Kakkonto was the formula most prescribed during the study period, followed by shoseiryuto and tokishakuyakusan. In the 180 days before pregnancy, the most prescribed medicine was tokishakuyakusan, followed by kakkonto and shoseiryuto. Shoseiryuto, tokishakuyakusan, and kakkonnto were the formulae most prescribed during pregnancy. The most prescribed medicines during the 180 days postpartum were kakkonto, shoseiryuto, and saireito. Conclusions: Information in the Japanese insurance system shows that Kampo medicines are often prescribed during pregnancy. Most of these prescriptions are generally used for the treatment of common cold. Tokishakuyakusan in particular is usually used in the treatment of various symptoms of pregnancy. Further research is needed to clarify the relationship between the use of Kampo medicines during pregnancy and adverse events in infants in Japan.